2014
DOI: 10.1016/j.rbr.2014.04.006
|View full text |Cite
|
Sign up to set email alerts
|

Tradução, adaptação cultural, validade e confiabilidade do questionário de classificação do ombro para uso no Brasil

Abstract: Psychometric criteria were found, which justify the applicability of the Brazilian version of SRQ in individuals with shoulder functional impairments.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…The results of the current study indicated that the SRQ-T is reliable and valuable in the evaluation of shoulder pain and is similar in terms of validity and reliability to other studies of SRQs for different populations. 19 , 27 , 28 Cronbach’s alpha coefficient score was above 0.70 for all questionnaires and domains. Also, the ICC values of the SRQ-T total scores were interpreted as having high reliability.…”
Section: Discussionmentioning
confidence: 84%
See 3 more Smart Citations
“…The results of the current study indicated that the SRQ-T is reliable and valuable in the evaluation of shoulder pain and is similar in terms of validity and reliability to other studies of SRQs for different populations. 19 , 27 , 28 Cronbach’s alpha coefficient score was above 0.70 for all questionnaires and domains. Also, the ICC values of the SRQ-T total scores were interpreted as having high reliability.…”
Section: Discussionmentioning
confidence: 84%
“…The SRQ has been translated into several languages and has been found to be valuable and reliable for different populations. 19 , 27 , 28 A validation study of the Korean version of the SRQ (SRQ-K) involved 52 participants and demonstrated Cronbach’s alpha for an internal consistency of 0.75. The test–retest reliability of the SRQ-K and the domains of the SRQ-K ranged from 0.84 to 0.95.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations